Home page for accesible maths 6 Chapter 6 contents

Style control - access keys in brackets

Font (2 3) - + Letter spacing (4 5) - + Word spacing (6 7) - + Line spacing (8 9) - +

6.33 Example continued

To obtain the solution to the inhomogeneous equation, we just have to find the PI. Since q(x)q(x) is a quadratic polynomial, then we have to look for a PI of the form

y=b2x2+b1x+b0.y=b_{2}x^{2}+b_{1}x+b_{0}.

To find the values of b2,b1,b0b_{2},b_{1},b_{0} we therefore just plug this polynomial into the differential equation to see what we obtain. We have y=2b2x+b1y^{\prime}={2b_{2}x+b_{1}} and y′′=2b2y^{\prime\prime}={2b_{2}}. To obtain equality in the differential equation, we therefore require:

6b2x2+(6b1+10b2)x+(6b0+5b1+2b2)=6x2+1.6b_{2}x^{2}+\left(6b_{1}+10b_{2}\right)x+\left(6b_{0}+5b_{1}+2b_{2}\right)=6x^% {2}+1.

Then we see immediately that b2=1b_{2}={1} and therefore, inspecting the linear term, that b1=-53b_{1}={\frac{-5}{3}}, and hence finally that b0=2218=119.b_{0}={\frac{22}{18}=\frac{11}{9}.} Adding PI and CF we obtain the general solution:

y=Ae-2x+Be-3x+x2-53x+119.y={Ae^{-2x}+Be^{-3x}+x^{2}-\frac{5}{3}x+\frac{11}{9}.}